A Hierarchy of Patient-Reported Outcomes for Meta-Analysis of Knee Osteoarthritis Trials: Empirical Evidence from a Survey of High Impact Journals. (26th June 2012) - Juhl, Carsten; Lund, Hans; Roos, Ewa M.; Zhang, Weiya; Christensen, Robin
Abstract : Objectives . To develop a prioritised list based on responsiveness for extracting patient-reported outcomes (PROs) measuring pain and disability for performing meta-analyses in knee osteoarthritis (OA). Methods . A systematic search was conducted in 20 highest impact factor general and rheumatology journals chosen a priori. Eligible studies were randomised controlled trials, using two or more PROs measuring pain and/or disability. Results . A literature search identified 402 publications and 38 trials were included, resulting in 54 randomised comparisons. Thirty-five trials had sufficient data on pain and 15 trials on disability. The WOMAC "pain" and "function" subscales were the most responsive composite scores. The following list was developed. Pain: (1) WOMAC "pain" subscale, (2) pain during activity (VAS), (3) pain during walking (VAS), (4) general knee pain (VAS), (5) pain at rest (VAS), (6) other composite pain scales, and (7) other single item measures. Disability: (1) WOMAC "function" subscale, (2) SF-36 "physical function" subscale, (3) SF-36 (Physical composite score), and (4) Other composite disability scores. Conclusions . As choosing the PRO most favourable for the intervention from individual trials can lead to biased estimates, using a prioritised list as developed in this study is recommended to reduce risk of biased selection of PROs in meta-analyses.